Foreign economic cooperation between Ukraine and EU countries on the agricultural market and food industry under the influence of financial and credit policy instruments - Gudz, Iurii; Tulush, Leonid; Pochernina, Nataliia; Nykonenko, Oksana; Sauliak, Oleksandr; Гудзь, Юрій Федорович; Тулуш, Леонід Дмитрович; Почерніна, Наталя Вікторівна; Никоненко, Оксана Анатоліївна; Сауляк, Олександр (Krakow : PTTZ, 2026)
EN: Background. Understanding structural shifts in Ukraine's agricultural exports, including raw materials for food processing and value-added food chains, is crucial for enhancing the competitiveness of its food industry. This study aimed to determine the impact of financial and credit policy and support mechanisms on structural changes in foreign economic cooperation between Ukraine’s agricultural sector and the European Union. The methodology included an analysis of official statistics for 2008 ÷ 2024, the construction of trade openness indicators, and a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis. Results and conclusions. The findings indicated a steady shift in the geography of Ukraine’s agricultural exports in favor of the European Union: its share increased from approximately 25 ÷ 30 % between 2008 and 2010 to 60 ÷ 66 % between 2023 and 2024, while the share of the Commonwealth of Independent States (CIS) declined to around 3 %. It was established that the export-to-import coverage ratio exceeded 1 between 2021 and 2022, indicating a positive trade balance, but fell to 0.66 in 2024 due to warrelated and logistical constraints. The dynamics of niche product exports were also analyzed: sugar exports reached around 700,000 tons, poultry meat exceeded 300,000 tons, honey amounted to 35,000 ÷ 50,000 tons, and juice exports were 10,000 ÷ 15,000 tons, significantly surpassing the tariff quotas. It was concluded that an adaptive financial and credit policy strengthens Ukraine’s position in the European Union market; however, further integration will require substantial investment in food processing, production modernization, and the development of high value-added food products meeting EU quality standards.
Keywords: foreign currency earnings; credit mechanisms; export; agricultural sector integration; food processing